Tinjauan Literatur Optimalisasi Manajemen Sumber Daya Manusia Untuk Peningkatan Produktivitas dan Keberlanjutan Peternakan Sapi Perah - Nisa, Natasya Khairun; Nabila, Citra; Azahra, Sabilinnisa; Apriliani, Fany (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
Human resources are the driving force of animal husbandry in Indonesia, because the role of human resources is important and aligned with qualified work skills will create sustainable dairy farms. This Literature Review aims to examine the effect of increasing productivity and sustainability of dairy farms through optimizing human resource management. This study used a systematic review method. After collecting information from 13 SINTA accredited journals and SCOPUS indexed journals, it was found that optimizing human resource management plays an important role in realizing productivity and sustainability of dairy cows, as found in this literature review that empowering farmers by providing training, knowledge and skills is a key factor in increasing production yields that support business sustainability.